2016
DOI: 10.1111/ipd.12228
|View full text |Cite
|
Sign up to set email alerts
|

Intracanal irrigants for pulpectomy in primary teeth: a systematic review and meta‐analysis

Abstract: More studies are required with adequate quality, as well as a full-result report, including summary measurements of both response variables and effect size, to determine the most effective irrigant agents for use in pulpectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 34 publications
0
24
0
3
Order By: Relevance
“…Pulpectomy is an endodontic technique recommended for the treatment of irreversible pulp inflammation or necrosis caused by dental trauma or caries and is considered a conservative option compared with tooth extraction. 4,5 The main goal of this endodontic intervention is to recover the function of the affected tooth by treating or preserving the integrity of the periapical tissue and to prevent subsequent reinfection by eliminating microorganisms from root canals. 6 Although most randomised clinical trials have reported satisfactory success rates for primary tooth pulpectomy, [7][8][9] these studies included procedures performed without sedation or general anaesthesia.…”
mentioning
confidence: 99%
“…Pulpectomy is an endodontic technique recommended for the treatment of irreversible pulp inflammation or necrosis caused by dental trauma or caries and is considered a conservative option compared with tooth extraction. 4,5 The main goal of this endodontic intervention is to recover the function of the affected tooth by treating or preserving the integrity of the periapical tissue and to prevent subsequent reinfection by eliminating microorganisms from root canals. 6 Although most randomised clinical trials have reported satisfactory success rates for primary tooth pulpectomy, [7][8][9] these studies included procedures performed without sedation or general anaesthesia.…”
mentioning
confidence: 99%
“…Full text retrieval was limited to 52 publications out of which 28 (Appendix ) were excluded due to absence of MA. Final selection identified 24 SRs with MA . The characteristics of the SRs with MA are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Among the study topics in Paediatric Dentistry, most of the SRs focused on preventive strategies (37.5%) followed by restorative procedures (16.6%), pediatric endodontic procedures (16.6%), and behavior management aspects (16.6%). On contacting the authors on the scores, eight out of 24 authors responded . Three authors agreed to the scores and five authors provided justification for changes in the scores.…”
Section: Resultsmentioning
confidence: 99%
“…The methodological quality and validity of the included studies were independently assessed by two blinded reviewers using Grading of Recommendations Assessment, Development and Evaluation (GRADE) (Atkins et al, ) and Oxford Centre for Evidence‐Based Medicine (OCEMB) (Howick et al, ) criteria, employing the table reported by Pozos‐Guillen, Garcia‐Flores, Esparza‐Villalpando, and Garrocho‐Rangel (), both considered suitable for reducing potential biases in terms of quality of RCTs (Pozos‐Guillen et al, ; Urrútia & Bonfill, ). The reviewers scored each scale section based on their judgment and knowledge, in order to determine the weight of the respective section in terms of the final results and conclusions of each individual study.…”
Section: Methodsmentioning
confidence: 99%